Burden of onchocerciasis-associated epilepsy: first estimates and research priorities - Natalie V. S. Vinkeles Melchers; Sarah Mollenkopf; Robert Colebunders; Michael Edlinger; Luc E. Coffeng; Julia Irani; Trésor Zola; Joseph N. Siewe; Sake J. de Vlas; Andrea S. Winkler; Wilma A. Stolk (BMC, 2018)
Abstract Background Since the 1990s, evidence has accumulated of an increased prevalence of epilepsy in onchocerciasis-endemic areas in Africa as compared to onchocerciasis-free areas. Although the causal relationship between onchocerciasis and epilepsy has yet to be proven, there is likely an association. Here we discuss the need for disease burden estimates of onchocerciasis-associated epilepsy (OAE), provide them, detail how such estimates should be refined, and discuss the socioeconomic impact of OAE, including a cost-estimate for anti-epileptic drugs. Main body Providing OAE burden estimates may aid prevention of epilepsy in onchocerciasis- endemic areas by inciting and informing collaboration between onchocerciasis control programmes and mental health services. Epilepsy not only massively impacts the health of those affected, but it also carries a high socioeconomic burden for the households and communities involved. We used previously published geospatial estimates of onchocerciasis in Africa and a separately published logistic regression model quantifying the association between onchocerciasis and epilepsy to estimate the number of OAE cases. We then applied disability weights for epilepsy to quantify the burden in terms of years of life lived with disability (YLD) and estimate the cost of treatment. We estimate that in 2015 roughly 117 000 people were affected by OAE across onchocerciasis-endemic areas previously under the African Programme for Onchocerciases control (APOC) mandate where OAE has ever been reported or suspected, and another 264 000 persons in onchocerciasis-endemic areas where OAE has never been investigated before. The total number of YLDs due to OAE was 39 300 and 88 700 in these areas respectively, based on a weighted mean disability weight of 0.336. The burden of OAE is approximately 13% of the total YLDs attributable to onchocerciasis and 10% of total YLDs attributable to epilepsy. We estimated that by 2015 the total costs of treatment with anti-epileptic drug for OAE cases would have been a minimum of 12.4 million US$. Conclusions These estimates suggest a considerable health, social and economic burden of OAE in Africa. The treatment and care for people with epilepsy, especially in hyperendemic onchocerciasis areas with high epilepsy prevalence thus requires more financial and human resources.